Laparoscopic cholecystectomy in situs inversus totalis: case report - Kota, Sreedhar Rao; Gundala, Abhilash; Sirikonda, Srikanth; Metta, Jayachandra Reddy; Jinde, Mayur Kumar (International Surgery Journal, 2019)
Laparoscopic cholecystectomy is one of the commonest surgical procedures carried out in the world today. Occasionally, few undiagnosed situs inversus patients present with calculous cholecystitis. One such case is being discussed here on how the diagnosis was made and focuses on the technical approach to the operation along with review of literature. A 52 year old female presented to our department with right hypochondrial pain which was diagnosed as choledocholithiasis and calculous cholecystitis with situs inversus totalis following clinical and radiological evaluation. Patient underwent ERCP and CBD, PD stenting, following which laparoscopic cholecystectomy was performed and the patient made uneventful recovery. Situs inversus with calculous cholecystitis is a rare entity. The surgeon must appreciate that care should be taken to set up the operating theatre in the mirror image of the normal set up for cholecystectomy. Surgerons must also modify their technique to adapt mirror image anatomy.